Considerations on Pain and Suffering in VestAndPage’s performance art - Monteiro, Felipe; Pagnes, Andrea (Repertório, 2019)
This text is formed from a series of detailed conversations with Andrea Pagnes of performance art duo VestAndPage (Italian artist Andrea Pagnes and German artist Verena Stenke) on the questions of pain, suffering and blood rituals in their performances. VestAndPage perform extreme physical acts in constrictive physical situations not to glorify pain, but as possibilities for a poetic encounter with suffering as a source of creativity, thus to liberate aesthetics from the justification of sacrifice. Drawing from their personal life experience, they translate their wounds into performative actions to seek authenticity and to speak about existential concerns belonging to mankind, the individual and society. Keywords: Body, Pain, Suffering, Blood, Performance art.